Exploration Study on Media Exposure and Maintenance of the 22nd Tour de Borobudur Sports Tour Activities 2022 - Zefanya, Calvin; Castyana, Billy; Rahayu, Tandiyo; Setyawati, Heny; Ali, Mohammad Arif; Anggita, Gustiana Mega; Yudhistira, Dewangga (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
In the holding of the 22nd Tour de Borobudur 2022, media exposure is considered to be one of the most important aspects of the event's success. Media exposure covers the sports tourism sector to attract audiences and encourage people to get to know and join the event. The main objective of this research is to find out how much media exposure there is at the 2022 Tour de Borobudur and what media gives the biggest exposure to the event. This research uses a research design that is exploration research with methods of retrieval of archive research data. The results of this study show that electronic media has 15 views and online media has 42 views. Exposure to the 2022 Tour de Borobudur event in the post-event period has the highest intensity of exposure, with a total of 35 online announcements. Online media, in the form of online news, is the primary source of exhibition for the 2022 Tour de Borobudur events compared to electronic media. So, online news has more potential than electronic media news and becomes the most recommended in the media display of the event due to the number of views given.